Sounds of the Borderland. Popular Music, War and Nationalism in Croatia since 1991 - A Ljubojevic (Slovo, 2012)
Ljubojevic, A (2012) Sounds of the Borderland. Popular Music, War and Nationalism in Croatia since 1991. [Ashgate Popular and Folk Music Series.] By CATHERINE BAKER. Pp. 278. Farnham: Ashgate. 2010. £60. Hardback. ISBN: 978-1-4094-0337-1. [Review]. Slovo , 24 (2) Click here to read the review.